COMPARISONAL CONTRIBUTION ANALYSIS OF REGIONAL TAX PAYMENTS BEFORE AND AFTER USING TAPPING BOX ON REGIONAL ORIGINAL INCOME (PAD) IN BANDAR LAMPUNG CITY - Rahmawati Herdian; Mohamad Fajri Mekka Putra (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The regulation of local tax payment policies with a manual system over time is increasingly ineffective for Bandar Lampung City Original Revenue. In 2018 the Bandar Lampung City Government made the latest breakthrough, namely paying local taxes using the Tapping Box, especially hotel taxes, restaurant taxes, entertainment and parking taxes, but problems arise in the use of the system. Regional tax payment arrangements with the system before and after using the Tapping Box in its application there are still taxpayers who do not comply with the payment arrangements. The contribution of local tax payments with the system before and using the Tapping Box needs to be increased in quantity and quality. Constraints and solutions in using the system before and after using the Tapping Box, the government must socialize the use of the Tapping Box to taxpayers who do not understand the benefits of using the tool and the government must supervise several tax objects.